2014
DOI: 10.1111/ans.12527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the sentinel lymph node in the SNAC-1 trial

Abstract: The combined technique resulted in a high identification rate. BD contributed to the identification of the SLNs in patients where LSG and GP failed to identify the sentinel node. Special attention to these techniques is needed in particular groups of patients such as those with high BMI, screen-detected primary tumours and tumour located in the inner quadrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…To maximize our SN identification rate, we used the dual method (radioactive tracer and patent blue dye). 25 - 29 Our identification rate was 97.6%, which is in accordance with most of the published literatures. 26 , 27 , 30…”
Section: Discussionsupporting
confidence: 91%
“…To maximize our SN identification rate, we used the dual method (radioactive tracer and patent blue dye). 25 - 29 Our identification rate was 97.6%, which is in accordance with most of the published literatures. 26 , 27 , 30…”
Section: Discussionsupporting
confidence: 91%
“…For 7 studies with a high proportion (≥90 %) [ 1 , 3 , 10 , 11 , 25 , 29 , 30 ], the pooled data revealed no statistically significant difference between dual tracers and radioisotope alone (OR = 1.41, 95 % CI 0.83–2.39, P > 0.05). For 6 studies with a relatively low proportion (<90 %) [ 19 , 21 23 , 26 , 31 ], the advantage of using dual tracers was statistically significant (OR = 2.99, 95 % CI 1.99–4.48, P > 0.05) (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Kuehn et al reported both data for patients before NAC and those after NAC, which were extracted separately [ 3 ]. For 6 studies including patients before NAC [ 1 , 3 , 11 , 21 , 31 , 34 ], the combined use of blue dye and radioisotope showed higher identification rate than radioisotope alone (OR = 2.96, 95 % CI 1.78–4.94, P < 0.05; I 2 = 15.6 %). For 3 studies including patients after NAC [ 3 , 20 , 27 ], no statistically significant difference was revealed when comparing dual tracers with radioisotope alone (OR = 1.53, 95 % CI 0.94–2.47, P > 0.05; I 2 = 31.6 %) (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations